Global burden, health inequalities and improvement gap of head and neck cancers in middle-aged and older adults from 1990 to 2021 - Minxia Yang; Feng Xuan; Xiaofeng Ma; Zhaoqi Qiu (PLoS ONE, 2025)
Background This study aimed to assess temporal trends, health inequities and potential improvements in the burden of head and neck cancer (HNC) in middle-aged and older adults between 1990 and 2021, focusing on three major subtypes: larynx, nasopharynx, and lip/oral cavity cancers. Methods A secondary analysis of the Global Burden of Disease Study (GBD) 2021 was performed, using age-standardised incidence rates (ASIR) and age-standardised disability-adjusted life years (ASDR) to quantify the burden of HNC. The average annual percent change was calculated to analyzed trends. The slope index of inequality (SII) and the concentration index quantified health inequities. Frontier analysis identified regions with potential for improvement. Result In 2021, there were approximately 650,205 new cases of overall HNC globally, resulting in 9,621,610 DALYs, with ASIR and ASDR both declining since 1990. ASIR exhibited a decrease for laryngeal and nasopharyngeal cancers, in contrast to an increase for lip and oral cavity cancers. ASDR decreased across all cancer types. The SII showed a notable shift in ASDR from countries with higher socio-demographic indices (SDI) in 1990 to those with lower SDI countries by 2021. Meantime, the concentration index revealed a worsening inequality in lower SDI countries. Frontier analyses across 204 countries and territories indicated that certain high SDI countries could effectively reduce ASDR for HNCs. Conclusion The global burden of HNCs shown considerable regional disparities. Health inequalities have persisted, with lower SDI regions bearing a heavier burden, particularly in laryngeal and lip/oral cavity cancers. Developing tailored national cancer control plans and enhancing international medical cooperation are essential to reduce HNC burden and promote equitable health outcomes.